Analysis of Competencies, Work Culture, and Work Facilities on the Performance of ASN Employees at the North Sumatra Provincial Education Office - Fashira Nisrina; Ikhah Malikhah; M. Chaerul Rizky (CV. Era Digital Nusantara, 2026)
This study aims to analyze the influence of competencies, work culture, and work facilities on the performance of ASN employees at the North Sumatra Provincial Education Office both partially and simultaneously. The type of research used is quantitative research with a causal associative approach. The research population is all ASN of the North Sumatra Provincial Education Office which totals 144 people, with the determination of the sample using the Slovin formula at an error rate of 10 5% so that a sample of 59 respondents was obtained which was selected through simple random sampling technique. The data collection technique used a questionnaire with a Likert scale of 1-5, while the data analysis technique used multiple linear regression analysis with the help of SPSS software which included validity test, reliability test, classical assumption test, t test, F test, and determination coefficient. The results of the study showed that: (1) competence had a positive and significant effect on employee performance with a calculated t value of 2.015 > t table 2.004 and a significance of 0.049 < 0.05; (2) work culture does not have a significant effect on employee performance with a t-value of 1.648 < t table 2.004 and a significance of 0.105 > 0.05; (3) work facilities have a positive and significant effect on employee performance with a t-value of 3.409 > t table 2.004 and a significance of 0.001 < 0.05, and are the most dominant variable; (4) competence, work culture, and work facilities simultaneously had a significant effect on employee performance with an F value of 9.201 > F table 2.77 and a significance of <0.001 < 0.05, with the ability to explain the variation in employee performance of 33.4% based on the R Square value, while the remaining 66.6% was explained by other variables outside the study.